Excavations in Iraq, 1985-1986 - Anonymus, A.
Tell Abu Dhahir; 'Ain Shayi' and al-Dakakin Cave; Borsippa (Birs Nimrud); Khirbet Deir Situn; Tell Deir Situn; Tell Dhuwaij; Tell Gir Matbakh; Tell Grai Darki; Khirbet Hatara; Isin (Ishan Bahriyat); Tell Jessary; Tell Jigan; Khirbet Karhasan; Larsa (Tell